1976
DOI: 10.1079/bjn19760061
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the appearance of a hepatic copper-binding protein in normal and zinc-deficient rats

Abstract: I . A study has been made by gel-filtration techniques of the soluble copper-and zincbinding proteins in rat liver after both intraperitoneal injection of Cu and dietary Cu supplementation.2. Liver Cu and Zn concentrations increased after injection of Cu, both metals accumulating in the cytosol, mainly in a fraction with an apparent molecular weight of about IZOOO.3. When Zn-deficient rats were injected with Cu, there was little change in liver Zn concentration and the occurrence of Cu in the low-molecular-wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…In contrast, the disappearance of metal from the copper-thioneins, as from the Zn2+-induced protein (Feldman & Cousins, 1976), proceeded at the same rate as the degradation of the protein. This suggests that these processes occurred concomitantly and therefore supports the claim (Bremner & Davies, 1976) that the failure of Zn2+-deficient animals to accumulate significant amounts of copper-thionein in their liver, regardless of their Cu2+ status, is a consequence of the decreased stability of the copper-thionein in these animals. This could be related to the decreased Zn2+ content of the Cu2+-induced metallothionein in these animals.…”
Section: Vol 174supporting
confidence: 66%
See 3 more Smart Citations
“…In contrast, the disappearance of metal from the copper-thioneins, as from the Zn2+-induced protein (Feldman & Cousins, 1976), proceeded at the same rate as the degradation of the protein. This suggests that these processes occurred concomitantly and therefore supports the claim (Bremner & Davies, 1976) that the failure of Zn2+-deficient animals to accumulate significant amounts of copper-thionein in their liver, regardless of their Cu2+ status, is a consequence of the decreased stability of the copper-thionein in these animals. This could be related to the decreased Zn2+ content of the Cu2+-induced metallothionein in these animals.…”
Section: Vol 174supporting
confidence: 66%
“…Injection of Cu2+ into rats has been shown to stimulate the incorporation of both copper and Zn2+ into a low-molecular-weight hepatic protein (Bremner & Davies, 1976), which was unequivocally identified as metallothionein (Bremner & Young, 1976b). The inhibitory effect of cycloheximide on this process indicated that active protein synthesis was involved (Bremner & Davies, 1976), although Bloomer & Sourkes (1973) suggested that the copper-protein was constitutive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notable in these studies was the observation that zinc uptake was prevented when rats had received prior administration of actinomycon D, a known inhibitor of mRNA synthesis. Although tissue levels of metallothionein are low in adults, its synthesis can be induced by different metals such as cadmium, zinc, copper, and mercury thus explaining their putative role as protective and storage proteins (5)(6)(7)(8). For example, synthesis of the thioneins takes place in liver, kidney, and spleen when animals are treated with sublethal doses of cadmium and certain other metallic salts (9).…”
mentioning
confidence: 99%